Responsibility of Parents In Islamic Education According To The Qur'an - Nahar, Syamsu; Salminawati, Salminawati; Diba, Latifah (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims: 1) Parental Responsibilities for Islamic Education in the Qur'an According to Tafsir Al-Misbah and Tafsir Al-Wasith, 2) Relevance of Parental Responsibilities for Islamic Education with Current Education. The type used in this research is qualitative research, namely research by means of descriptions in the form of words and language in a special natural context by utilizing various scientific methods that aim to provide explanations through the method of library research. The results of the study show that: 1) Parental Responsibilities for Islamic Education in the Qur'an According to Tafsir Al-Misbah and Tafsir Al-Wasith are found in: 1) Q.S. Al-Anfal Verses 27-28 (Responsibility of Faith Education), 2) Q.S. Ash-Shfft Verse 102 (Responsibility of Akhak and Intellectual Education), 3) Q.S. Luqman Verse 12-19 (Responsibility of Moral Education), 4) Q.S. At-Tahrim Verse 6 (Responsibility of Faith Education). 2) The relevance of parental responsibility in educating early childhood is that parents should feel worried if their offspring are weak so that every parent is required to form a quality generation with physical and spiritual education, including inviting children to play sports and play. Parents are encouraged to implement faith education, moral education and intellectual education for their children because later these parents will be held accountable in the afterlife. To apply Aqidah and faith education to children, one of them is by introducing the understanding that God created all creatures. Shows that parents always educate children with good morals in terms of words and deeds.